A method for evaluating the effects of allograft sterilization procedures on the viability of human fibroblasts. Issue 5 (September 1974) - Chalcroft, S. C. W.; Gavin, J. B.; Seelye, R. N.
Abstract : Chalcroft, S. C. W., Gavin, J. B., and Seelye, R. N. (1974). Thorax, 29, 539-544. A method for evaluating the effects of allograft sterilization procedures on the viability of human fibroblasts. A semiquantitative method for assessing the effects of allograft sterilization procedures on the viability of cultured human fibroblasts is described. The proportions of `viable', `altered', and `non-viable' cells in four groups of fibroblasts on coverslips were estimated using light microscopy and their staining reactions with neutral red and nigrosin. While a control group of fibroblasts remained viable, exposure for one to three weeks to each of three solutions used in allograft preparation produced a progressive transition first to the altered and then to the non-viable category. These findings were confirmed by electron microscopic examination of similarly treated cells grown on millipore filters. Applications of the method are discussed.